1995
DOI: 10.1002/chin.199516013
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Dinitramide and Its Salts. Part 4. Molecular Structure of Dinitramide.

Abstract: Dinitramide and Its Salts. Part 4. Molecular Structure of Dinitramide. --(SHLYAPOCHNIKOV, V. A.; CHERSKAYA, N. O.; LUK'YANOV, O. A.; GORELIK, V. P.; TARTAKOVSKII, V. A.; Izv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…HPLC/ultraviolet (UV) analysis demonstrated that, in aqueous solution, the FOX-12 salt dissociates instantly to its two components, guanylurea and dinitramide. The HPLC chromatogram at 210 nm in Figure clearly shows two peaks: one appearing at a retention time of 5.8 min identified as guanylurea by comparison to a reference standard material and another appearing at 9.1 min identified as dinitramide and confirmed by liquid chromatography–ultraviolet/mass spectrometry (LC–UV/MS) showing characteristic UV absorptions at 219 and 285 nm ,, and a deprotonated molecular mass ion [M – H] at 106 Da.…”
Section: Resultsmentioning
confidence: 99%
“…HPLC/ultraviolet (UV) analysis demonstrated that, in aqueous solution, the FOX-12 salt dissociates instantly to its two components, guanylurea and dinitramide. The HPLC chromatogram at 210 nm in Figure clearly shows two peaks: one appearing at a retention time of 5.8 min identified as guanylurea by comparison to a reference standard material and another appearing at 9.1 min identified as dinitramide and confirmed by liquid chromatography–ultraviolet/mass spectrometry (LC–UV/MS) showing characteristic UV absorptions at 219 and 285 nm ,, and a deprotonated molecular mass ion [M – H] at 106 Da.…”
Section: Resultsmentioning
confidence: 99%
“…Solving the system of Eqs. (1), (2) and (3), one can obtain expression for the concentrations of the anions, molecules and protonated form of HDN. At the great difference in the constants of the decomposition of these forms there are three regions of the acidity of sulfuric acid solutions, where the rate of the decomposition is determined by the rate of the decomposition of only one equilibrium form: N(NO 2 ) À 2 , HN(NO 2 ) 2 or H 2 N(NO 2 ) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The ammonium dinitramide (ADN), as a new generation of the high energy oxidizer, is considered to be a preferable alternative to the traditional ammonium perchlorate (AP) oxidizer because of the advantage of positive oxygen balance and low characteristic combustion signal [1][2][3][4][5][6][7][8][9]. Therefore, ADN has attracted a great deal of interests in the energetic materials community.…”
Section: Introductionmentioning
confidence: 99%